Percepção da RDA pelos catalogadores para implementação nas bibliotecas da Universidade Federal de Minas Gerais - Paulo Marcelo Carvalho Holanda (2020)
The recent information and communication technologies (ICTs) brought changes in the information environments that contributed to the appearance of new types of documents, formats, supports, content and new ways of accessing information and, with that, a new way of registering resources. In this way, the new cataloging standard appears that will replace AACR2, the RDA, which is a reality already used by several libraries in other countries. For the implementation, it is necessary that the catalogers that work in the front line of the information record, understand the changes coming from the GDR, its structure, focus, scope, instructions and its relation to AACR2 and the MARC 21 format, to later apply the standard RDA in its technical work routine, to then adopt it. Faced with this scenario, the question arises: how do the catalogers of the UFMG library units perceive the RDA standard today? This study aims to understand the current reality of perception of the catalogers of the technical processing Sectors of the library units of the Federal University of Minas Gerais in the face of the new cataloging standard, as well as the general view of the standard, their understanding of changes in the instructions for describing the resource data, its international context, its awareness of the strategies for preparing the implementation of the RDA, the familiarity with the topics of the RDA and the models that compose it. The methodology has exploratory and descriptive characteristics while the approach presents aspects of mixed methods, which are an investigation approach that combines or associates qualitative and quantitative forms. Interviews (semi-structured) around four thematic blocks were used as a data collection technique: 1. General impression of the RDA standard; 2. Topics of change in the RDA; 3. Preparation for the implementation of the RDA and 4. Preferences of topics for training and data analysis, the content analysis methodology for the explanation and systematization of the collected content, and for data interpretation and discussion, the categorization. The results point to a greater understanding of the general impression issues of the RDA and less familiarity of the catalogers with the topics of change and with the preparation for the implementation of the RDA. The study presents some necessary steps for a good implementation of the RDA that can be applied by UFMG libraries and other libraries. It is concluded that the need to learn about the changes and characteristics that make up the RDA, mainly the practical demonstration of its operation, as well as training practices that reaffirm awareness for knowledge of the standard is essential for its implementation.